Evaluasi Capaian Hafalan Al-Qur’an Santri pada Lembaga Tahfidz Intensive Center Medan - Asdia Harahap; Sakban Lubis; Nanda Rahayu Agustia (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2026)
This study examines the effectiveness of Qur’anic memorization achievement and the factors contributing to variations in students’ tasmi’ performance at Tahfidz Intensive Center Medan. The research addresses how memorization outcomes are achieved within the tahfidz learning process and identifies the supporting and inhibiting factors influencing students’ performance. A descriptive qualitative approach was employed involving ten students aged 14–20 years who participated in six-month and one-year ziyadah programs. Data were collected through observation, structured interviews, and documentation, then analyzed using data reduction, data display, and conclusion-drawing techniques. The findings reveal that the implementation of the tikrar method, routine muroja’ah, a disciplined learning environment, structured halaqah schedules, and strong internal and external motivation significantly support students’ memorization achievement. The study also identifies several obstacles, including fatigue, boredom, inconsistent muroja’ah, and limited family support, which negatively affect memorization retention and performance consistency. The study argues that successful Qur’anic memorization achievement depends not only on methodological effectiveness but also on continuous supervision, psychological readiness, and sustained motivational support within the educational environment.